2021
DOI: 10.1177/2374373521996958
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspective on Iron Chelation Therapy: Barriers and Facilitators of Medication Adherence

Abstract: Nonadherence to iron chelation therapy (ICT) remains a long-standing and serious issue in thalassemia, especially in resource-constrained developing countries. Barriers and facilitators of adherence to ICT in transfusion-dependent thalassemia (TDT) adult patients in Malaysia are not completely understood. This qualitative study explored factors affecting adherence to ICT among TDT adult patients at a public tertiary hospital in Malaysia. Data were collected through 21 semistructured in-depth interviews conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…The variation in our study may be explained by the disparity in patients’ attitude and belief towards illness and treatment. This may include fatalistic attitude towards their illness that has been previously documented as a potential cause of poor adherence and may also be the reason behind high DRP ( Saidi et al, 2018 ; Chong et al, 2021 ). Intriguingly, there is a culture of using alternative medicine as naturally available products were perceived to be more effective and safer for consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in our study may be explained by the disparity in patients’ attitude and belief towards illness and treatment. This may include fatalistic attitude towards their illness that has been previously documented as a potential cause of poor adherence and may also be the reason behind high DRP ( Saidi et al, 2018 ; Chong et al, 2021 ). Intriguingly, there is a culture of using alternative medicine as naturally available products were perceived to be more effective and safer for consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Patients perceiving medication-taking as routine, using breakfast/other meals as reminders, the realization of the need to live longer, having a positive mindset, and making efforts to avoid complications motivated them to adhere to medications. Some studies reported family support, having medication pill boxes, having insight of their illness, low medication burden, and having enabling environment as facilitators of medication adherence (29,30). Intervention focused on reminders have the potential to improve adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The most common obstacle in enhancing chelation compliance is patient-related, such as a lack of psychological willingness and belief in their ability in administering ICT, which is often due to failure in regulating their negative emotions. [4] The estimated mean rate of patients' compliance of desferrioxamine (DFO) is often dissatisfactory, ranging from 59 to 78% [5]. Low compliance to iron chelation therapy jeopardises treatment effectiveness, resulting in significant morbidity and mortality, reducing patients' health-related quality of life, as well as higher expenses to manage iron overload complications.…”
Section: Introductionmentioning
confidence: 99%